What Shapes User Expectations? Exploring Reliability, Simplicity, and Security in Digital Payments - Mira; Tjahjadi, Bambang (Universitas Medan Area, 2025)
As digital payment systems become increasingly integrated into everyday transactions, understanding user expectations and perceptions has become critical for service innovation and adoption. This study investigates how perceptions of benefits, convenience, and risk influence user expectations of digital payment systems among university students. Using a quantitative approach, data were collected via questionnaires from 96 accounting students at the University of Muhammadiyah Makassar, selected from a population of 2,770 using Slovin’s formula. SmartPLS 3.0 software was employed to analyze the structural model through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that perceptions of benefits, convenience, and risk all have significant positive effects on digital payment expectations. Additionally, the study examines the moderating role of user experience duration. Results show that user experience significantly moderates the relationship between benefit perception and expectations, as well as between risk perception and expectations, but does not moderate the relationship between convenience perception and expectations. These insights underscore the importance of trust and familiarity in shaping digital payment expectations, particularly among experienced users. The study contributes theoretically by integrating trust and perception frameworks, and methodologically by offering a structured approach to analyzing expectation formation in digital financial services.